The Implication of Traditional Value and Japanese Culture in Global Competition Era - Justien R.R. Wuisang (AIBPM Publisher, 2020)
Customary tradition or tradition for Japanese society is something that is very firmly held, tradition for them is not a matter of packaging as far as the eye can physically see it but rather how the spirit or enthusiasm combines between the will to progress in the spirit of maintaining culture. In this context, traditional symbols can be lost, but the spirit always remains and unites in the body and soul. Japanese people can say I'm Japanese even though my hair is colorful; Likewise with very high discipline, Japanese people are hard-working, enthusiasm is obtained from samurai teachers who are sent down by traders, the spirit of samurai is inspiring and united in itself, forming the personality of Japanese people who never give up. Japan is very strong with its traditions until now, they are a society that is anti-lying, identity is the most important. Culture is human creativity, works that are always in process, dynamic, are the unity obtained together from the existing environment, while tradition is information that is passed on from generation to generation for generations both written and verbally, without this continuity, not tradition and one day it ends. Japan combines the traditional values of the Japanese people that are deeply rooted in the lives of their people with management principles obtained from the Western world and especially America. The values of the Japanese tradition are in line with the beginning of Japanese civilization, some of which are family, group solidarity, belonging, loyalty or loyalty, diligence, willingness to work hard, pride and shame.